2022
DOI: 10.3389/fnbeh.2022.788633
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Senses Modulate Food Consumption and Physiology in Drosophila melanogaster

Abstract: Both sensory and metabolic processes guide food intake. Olfactory inputs help coordinate food appreciation and selection, but their role in food consumption and post-feeding physiology remains poorly understood. In this study, using Drosophila melanogaster as a model system, we investigated the effects of olfactory sensory neurons (OSNs) on food consumption, metabolism, and stress responses. We found that dysfunction of OSNs affects diverse processes, including decreased food consumption, increased triacylglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The presence of Ehrlich degradation pathway in specific microbes and many insect attracting plants underscores the importance of odors in mediating interkingdom interactions. IAA, in combination with other odors, has been reported to attract Drosophila melanogaster and help in establishing a fly-fruit-yeast relationship [68][69][70][71][72][73][74] . Why do animals need BCAA?…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Ehrlich degradation pathway in specific microbes and many insect attracting plants underscores the importance of odors in mediating interkingdom interactions. IAA, in combination with other odors, has been reported to attract Drosophila melanogaster and help in establishing a fly-fruit-yeast relationship [68][69][70][71][72][73][74] . Why do animals need BCAA?…”
Section: Discussionmentioning
confidence: 99%
“…As hunger can initiate multiple downstream signaling processes based on nutritional conditions like sensory perception etc., inducing hunger may change the signaling process involved in feeding. 9 , 10 The result of such an experiment is always bound to be a hunger induced feeding assay. Further, the flies start defecating ingested food post 30 min of feeding and thus this assay cannot be used to understand long term feeding behaviors.…”
Section: Before You Beginmentioning
confidence: 99%
“…It is previously shown that flies prefer alcohol-laced food. 9 To test 2-choice feeding we used Canton S flies tested for 20% alcohol along with 0.1M sucrose solution (green color solution) and 0.1M sucrose solution without alcohol (red color solution). As we are measuring food preferences, some flies may choose both the available choices and to recognize this we need to use colors such that the secondary color may be easily visualized.…”
Section: Expected Outcomesmentioning
confidence: 99%